Pendekatan Pembelajaran Berbasis Gaya Belajar dan Pembelajaran Berdiferensiasi dalam Pendidikan Agama Islam dengan Metode Service Learning - Santi, Santi; Muhammad Redha Anshari; Siti Suwarni (Yayasan Literasi Sains Indonesia, 2024)
This article discusses the application of a learning style-based learning approach and differentiated learning in Islamic Religious Education (PAI) subjects using the service learning method. This approach is designed as a form of service to increase students' understanding of the subject matter in depth and at the same time as being applicable in everyday life. The main material focus includes the concept of Faith, the principle of a useful life which stresses the importance of avoiding negative behavior such as extravagance, riya', sum'ah, takabur, and hasad, as well as deepening understanding of the role of Insurance, Banks, and Sharia Cooperatives in supporting the economy of the people based on Islamic values. Through this service, students not only understand the material theoretically, but are also invited to integrate spiritual, moral and social values ​​into real practice. The results of the service are proven by the increasing depth of students' understanding of the material, as seen from their ability to explain, apply and instill Islamic values ​​in everyday life. Thus, this method is an innovative solution to optimize learning while instilling useful values ​​in students' daily lives.